Elaboración de un Musicograma para el desarrollo sensorial de los niños y niñas - Estrella Pallo, Ana Lucia (2022)
The purpose of this study is to design musicograms as didactic resources to enhance the development of the sensory organs of high school infants of the Educational Unit "19 de Septiembre. Based on the problem, the elaboration of musical activities was encouraged in order to promote the use of musicograms, in class hours considering an innovative and creative method, which will help to enhance their motor and cognitive skills. The research methodology was framed in the qualitative approach, inductive method, bibliographic-documentary design and the application of field information sources, among the techniques and tools used were; the interview, observation sheet and focus group, was based on the constructivist pedagogical approach for the elaboration of educational resources with different designs of musicograms, in order to achieve attention in the boys and girls of the Educational Unit in this way it will allow Correctly stimulate the sensory organs and at the same time enhance fine and gross motor skills. In addition, it will improve musical perception by facilitating the understanding, monitoring and analysis of the different musical activities, in order to promote musical art and comprehensive development. Therefore, the proposal "I play, I have fun and I learn with the senses" was designed; That it be based on ten musical activities for the development of the sensory organs in which didactic, recyclable and environmental materials are used, in the same way a drive was created as a tutorial resource pointing out each activity where it will generate great expectation and emotion to learn.